PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENTÂ TEAMSÂ ACHIEVEMENTÂ DIVISION (STAD) TERHADAP HASIL BELAJAR SEPAK MULA BAWAH PADA PERMAINAN SEPAK TAKRAW (STUDI PADA SISWA KELAS XI B SMK 1 MUHAMMADIYAH TRENGGALEK) - DEWIANTARI, RESTYAN (Jurnal Pendidikan Olahraga dan Kesehatan, 2014)
Abstract To get plays good takraw kick up, someone respondenting to have ability or good skill. In takraw's kick up there is two tech kicks up beginning (service) which is beginning kick up down and up.  Effort increases skill play kick up takraw shall do training systematically and kontinyu.  A teacher has to have skill and innovation in give learning material kicks up takraw so pleasing student in do learning process, that thing gets to be rendered by one of the ways which is apply kooperatif's learning model which is learning which performed by shoal ala. kooperatif STAD's learning model expected by anxious more student and motivated deep follow physical education study in particular on material kicks up takraw because student is asked out is cooperative deep little groups and talk over its material. Prescribed agglomerate success by all group member. It enables all agglomerate member come on to get active role in learning activity. So no more student which passive in processes physical education especially in follow takraw's kick up study. To the effect this research is: to know and how big kooperatif's learning model type STAD can increase studying result kicks up bottom beginning on game kicks up takraw on student brazes XI SMK 1 Muhammadiyah Trenggalek.  Observational type is pseudo experiment, with quantitative descriptive approaching. Observational target on student brazes XI B SMK 1 Muhammadiyah Trenggalek as much 39 students. Downloading was done to essay beginning kick up down. Observational result can be concluded that learnings model Implement kooperatif type student teams achievement division  (STAD) can increase studying result kicks up bottom beginning on game kicks up takraw with increasing as big as 137,64%. Result tests t( Paired Sample t Test ) declare for that point t computing  20,84> point t table  2,021, its mean is implemented model kooperatif's learning type student teams achievement division  (STAD) having for positive and signifikan to usufruct beginning kick up studying down on game kicks up takraw. Keywords: Implement, STAD'S learning, Beginning Kick up Down.